‘Ulama’s Perceptions of Women Involvement in Politics in South Aceh - Desi Purnama Sari (Program Doktor Akidah dan Filsafat Islam, 2020)
This research aims to reveal how women are involved in politics in South Aceh, factors influencing Ulama’s opinions about the women involvement in politics, and also their perceptions about the involvement. Method used in this research was qualitative (field research), through interviews and observations, then literature research (library research). Dataobtained in the field were interpreted through descriptive analysis. The results show several things. Firstly, the women involvement in South Aceh politic had developed, such as serving as a member of Parliament, candidates, secretary, and chief of the committee. Secondly, ulama’s perceptions about the involvement of women in politics are that some Ulama allow women participated in politics. Nevertheless, women must maintain their identity as a Muslim. On the other hand, some ulama reject women involvement in politics because many obstacles would be faced by women who are less firm in the leadership and decision making. Thirdly, a fewfactors that cause the differences in ulama’s perception of women’s involvement in South Aceh politics are due to differentinterpretations of al-Qur’an verses and hadith. Other reasons are that some Ulamado not know about politics, and some are related to their educational level and their knowledge.